Echinacea purpurea: Pharmacology, phytochemistry and analysis methods - Manayi, Azadeh; Vazirian, Mahdi; Saeidnia, Soodabeh (Pharmacognosy Reviews)
Echinacea purpurea (Asteraceae) is a perennial medicinal herb with important immunostimulatory and anti‑inflammatory properties, especially the alleviation of cold symptoms. The plant also attracted scientists’ attention to assess other aspects of its beneficial effects. For instance, antianxiety, antidepression, cytotoxicity, and antimutagenicity as induced by the plant have been revealed in various studies. The findings of the clinical trials are controversial in terms of side effects. While some studies revealed the beneficial effects of the plant on the patients and no severe adverse effects, some others have reported serious side effects including abdominal pain, angioedema, dyspnea, nausea, pruritus, rash, erythema, and urticaria. Other biological activities of the plant such as antioxidant, antibacterial, antiviral, and larvicidal activities have been reported in previous experimental studies. Different classes of secondary metabolites of the plant such as alkamides, caffeic acid derivatives, polysaccharides, and glycoproteins are believed to be biologically and pharmacologically active. Actually, concurrent determination and single analysis of cichoric acid and alkamides have been successfully developed mainly by using high‑performance liquid chromatography (HPLC) coupled with different detectors including UV spectrophotometric, coulometric electrochemical, and electrospray ionization mass spectrometric detectors. The results of the studies which were controversial revealed that in spite of major experiments successfully accomplished using E. purpurea, many questions remain unanswered and future investigations may aim for complete recognition of the plant’s mechanism of action using new, complementary methods.
Keywords: Analysis methods; anti‑inflammatory; clinical trial; cytotoxic; Echinacea purpurea; immunomodulatory; psychotic